Retrospective evidence on outcomes and experiences of pregnancy and childbirth in epidermolysis bullosa in Australia and New Zealand - Lizbeth R.A. Intong, MD, DPDS, FACD; S. Deanne Choi, MBBS; Alexa Shipman, BMBCh, MRCP; Yong C. Kho, MBBS; Shelley J.E. Hwang, MBBS; Lesley M. Rhodes, SRN; Judie R. Walton, PhD; Michael G. Chapman, MBBS, MD, FRCOG, FRANZCOG; Dédée F. Murrell, MA, BMBCh, MD, FAAD, FACD, FRCP (Wolters Kluwer, 2017)
Background: Pregnancy in epidermolysis bullosa (EB) has not been comprehensively studied. Objective: We aimed to develop a foundational database, which could provide peri-obstetric advice in EB. Methods: Survey questionnaires were sent to obstetricians, unaffected mothers of EB babies, and mothers with EB. Results were analyzed using chi-square, Fisher exact, and t-tests. Results: Out of 1346 obstetricians surveyed, 195 responded, and only 14 had encountered EB. All recommended normal vaginal delivery (NVD), except for one elective Caesarean section (CS). We received responses from 75 unaffected mothers who had delivered EB babies. They had significantly more complications in their EB pregnancies compared to their non-EB pregnancies. A further 44 women with various types of EB who had given birth responded. Most delivered via NVD and had no significant increase in complications in both their EB and non-EB pregnancies. In both groups, there were no significant differences in blistering at birth in babies delivered via NVD and CS. Conclusion: In conclusion, most patients with EB who are capable of giving birth do not have an increased risk for pregnancy-related complications and NVD appears to be safe. Awareness of this data amongst obstetricians and dermatologists should lead to improved quality of care for mothers and babies affected with EB. Keywords: Epidermolysis Bullosa, Pregnancy, Delivery, Childbirth, Anesthesia